Unravelling the physiological role and molecular function of betaine-sensitive nicotinic receptors of Caenorhabditis elegans - Turani, Ornella (2021)
The free-living nematode Caenorhabditis elegans is a model of parasitic nematodes. It has one of the most extensive nicotinic receptor (nAChR) families. However, the molecular functional properties and roles of many of these nAChRs remained unknown. ACR-23 is a nAChR present in neuronal and muscle cells of nematodes and it is not conserved in vertebrates. It is a cation-selective channel activated by betaine (BE) and sensitive to monepantel (MNP), a novel anthelmintic drug. Given the limited information about its functional role in nematodes, we explored ACR-23 from a physiological and molecular perspective. Locomotion assays of adult worm showed that BE significantly increased their motility. This effect was not observed in acr-23 mutants, indicating that BE acts through ACR-23. Interestingly, BE did not affect L1, indicating differential sensitivity between stages, probably arising from changes in ACR-23 expression levels during development. MNP decreased worm motility in the adult stage in a concentration-dependent manner with an EC50 of ~30 µM. The acr-23 mutant showed different MNP sensitivity compared to the wild-type strain, indicating that besides ACR-23 other receptors may be targeted by MNP. By using a primary culture of C. elegans muscle cells, we described for the first time the properties of BE-elicited single-channel currents. Our study provides insights into the molecular basis of anthelmintic action, which pave the way for the development of novel drugs.